154k views
0 votes
prove the following identity: sec x csc x(tan x + cot x) = 2+tan^2 x + cot^2 x please provide a proof in some shape form or fashion :/

User Kame
by
7.1k points

1 Answer

4 votes

Answer:

Explanation:

Hello,

Is this equality true ?

sec x csc x(tan x + cot x) = 2+tan^2 x + cot^2 x

1. let 's estimate the left part of the equation


sec(x)csc(x)(tan(x) + cot(x)) =(1)/(cos(x)sin(x))*((sin(x))/(cos(x))+(cos(x))/(sin(x)))\\\\=(1)/(cos(x)sin(x))*((sin^2(x)+cos^2(x))/(sin(x)cos(x)))\\\\=(1)/(cos(x)sin(x))*((1)/(sin(x)cos(x)))\\\\\\=(1)/(cos^2(x)sin^2(x))

1. let 's estimate the right part of the equation


2+tan^2(x) + cot^2(x)=2+(sin^2(x))/(cos^2(x))+(cos^2(x))/(sin^2(x))\\\\=(2cos^2(x)sin^2(x)+cos^4(x)+sin^4(x))/(cos^2(x)sin^2(x))\\\\=((cos^2(x)+sin^2(x))^2)/(cos^2(x)sin^2(x))\\\\=(1^2)/(cos^2(x)sin^2(x))\\\\=(1)/(cos^2(x)sin^2(x))

This is the same expression

So

sec x csc x(tan x + cot x) = 2+tan^2 x + cot^2 x

hope this helps

User Mohammad Roshani
by
5.9k points